2016
DOI: 10.1177/1367006915586586
|View full text |Cite
|
Sign up to set email alerts
|

Cognate identification methods: Impacts on the cognate advantage in adult and child Spanish-English bilinguals

Abstract: Objectives: The purpose of this study was to determine whether four different cognate identification methods resulted in notably different classifications of cognate status for Peabody Picture Vocabulary Test-Third Edition (PPVT-III) test items and to investigate whether differences across criteria would impact findings of cognate effects in adult and preschool-aged Spanish-English bilingual speakers. Methodology: We compared four cognate identification methods: an objective criterion based on phonological ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Our second hypothesis was that phonological similarity between the English words and their Dutch translations would positively influence pupils scores on the PPVT-4, as a cognate effect had already been shown for Spanish children (Potapova, Blumenfeld, and Pruitt-Lord 2016). Moreover, we expected that this effect would be larger for older pupils, as previous research had shown that older Dutch-Frisian bilingual children are better at recognising overlap between words in two languages than younger children (Bosma et al 2016).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Our second hypothesis was that phonological similarity between the English words and their Dutch translations would positively influence pupils scores on the PPVT-4, as a cognate effect had already been shown for Spanish children (Potapova, Blumenfeld, and Pruitt-Lord 2016). Moreover, we expected that this effect would be larger for older pupils, as previous research had shown that older Dutch-Frisian bilingual children are better at recognising overlap between words in two languages than younger children (Bosma et al 2016).…”
Section: Discussionmentioning
confidence: 91%
“…The researchers mentioned that this may have helped monolingual children with word association and recognition. Previous research has also shown that the PPVT-3 and PPVT-4 contain Spanish-English cognates (Potapova, Blumenfeld, and Pruitt-Lord 2016;Wood and Pena 2015), and that Spanish-English bilingual children perform better on cognates than on non-cognates (Potapova, Blumenfeld, and Pruitt-Lord 2016). Furthermore, a recent study with adult L2 learners showed that the PPVT-4 contains more French-English than Polish-English cognates, and hence French L1 speakers obtained higher scores on the PPVT-4 than Polish L1 speakers (Leśniewska, Pichette, and Béland 2018).…”
Section: L1 Effects When Investigating L2 Vocabularymentioning
confidence: 95%
See 2 more Smart Citations
“…Consistently, Bartolotti and Marian (2016) taught fluent speakers of English and German a novel artificial language that had overlap with both their L1 and L2, and found that both previously learned languages contributed to success with the novel language. Finally, in proficient speakers, structurally similar aspects of languages continue to provide cross-linguistic scaffolding for processing in both bilingual contexts (e.g., Costa et al, 2005;Schoonbaert et al, 2007;Blumenfeld et al, 2016a;Potapova et al, 2016) and multilingual contexts (e.g., Lemhöfer et al, 2004 been well established in young adults that previously known languages provide an experiential baseline that can facilitate the acquisition of novel languages, both through direct transfer of knowledge and through potential honing of cognitive skills that underlie learning (e.g., Hirosh and Degani, 2017). Consistently with predictions that older adults may rely heavily on previous knowledge, Marcotte and Ansaldo (2014) found in their word-level training study, teaching Spanish words to younger and older French monolinguals, that older learners had more robust cognate effects than the younger learners.…”
mentioning
confidence: 99%